Implementasi Sistem Monitoring dalam Meningkatkan Pelayanan Publik pada Dinas Spmdp2a Kabupaten Nias - Elvin Lase; Heseziduhu Lase (Dinasti Review, 2024)
Current advances in science and technology have penetrated government institutions in every public service. It is hoped that this will be able to handle service problems which have previously seemed complicated and convoluted. Public services are essentially to create security, comfort and social welfare for the community. This is the main reason for the SPMDP2A Service, not only is the issue of welfare, empowerment and protection of women and children also a priority scale for the SPMD2A Service. However, actualization in the field proves that there is still weak supervision of services at the SPMDP2A Service, there are many people in Nias Regency who complain about delays in handling problems, delays in distributing PKH funds and other social security, even employees tend not to respond well to the community. This research aims to determine the extent to which the implementation of the monitoring system that has been implemented at the SPMDP2A Service has improved public services. This type of research uses qualitative methods with a descriptive approach. The results of this research show that the SPMDP2A Service has implemented a monitoring system but it is not optimal, this is because monitoring can only be carried out manually, so that public services experience obstacles and limitations in implementation. The suggestions from this research are that it is hoped that the government will be able to prioritize a technology-based monitoring system so that it can support every public service in the SPMDP2A Service.